PEMBINAAN TARI REJANG MENDAK SIWI PADA IBU-IBU PKK, DESA PEJENG KAWAN, KECAMATAN TAMPAKSIRING, KABUPATEN GIANYAR - Gusti Ayu Made Puspawati; Luh Putu Pancawati; Ni Made Pira Erawati; Komang David Darmawan (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
The Rejang Mendak Siwi dance is a wali dance in Pejeng Kawan Village, Tampaksiring, Gianyar. This dance is danced during the piodalan ceremony which is held at Purnama Sadha. Where this dance can be danced by PKK women in Pejeng Kawan village at Agung Batan Bingin Temple. The Rejang Mendak Siwi dance created in 2020 by I Ketut Rena depicts expressions of gratitude, devotion, sincerely welcoming the arrival of the Gods by offering flower essence through symbolic, rhythmic, and beautiful movements. Rejang Mendak Siwi dance can be danced anywhere as long as it is a religious ritual. The Mendak Siwi Rejang dance training was carried out so that the women of the Pejeng Kawan village community knew the movements and patterns of the Rejang dance, especially the Mendak Siwi Rejang Dance. The purpose of coaching Mendak Siwi Rejang Dance, among others: To provide understanding and motivate women to be more active in dancing Mendak Siawi Rejang Dance. Transfer knowledge about the art of dance, especially Mendak Siwi Rejang Dance To foster creativity and confidence of PKK women in dancing Rejang Mendak Siawi. The expected outputs of this activity are: Attracting public interest, especially women from Pejeng Kawan village, to preserve the arts, especially the art of Rejang Mendak Siwi dance and ultimately love the nation's culture. Able to perform Mendak Siwi's rejang dance in accordance with the existing standards in the piodalan ceremony at Agung Batan Bingin Temple, Pejeng Kawan Village, Tampaksiring, Gianyar.